การพัฒนาถุงพลาสติกแผ่นฟิล์มรองเลือดในระยะคลอด The development of plastic film collector bag for postpartum blood loss during delivery - Anusornteerakul, Soiy (วารสารพยาบาลศาสตร์และสุขภาพ, 2015)
The purpose of this study is to develop a plastic film collector bag to assess blood loss during delivery. The sample were 100 of pregnant women who attend the antenatal care clinic and delivery in Tha Uthen Hospital, Amphoe Tha Uthen, Nakhon Phanom Province that without complications during pregnancy and childbirth. The instruments that used in the manufacture of plastic film collector bag consist of plastic film pack wrapped in medical supplies at one side of a sheet of plastic film. The other side of the paper. The instruments of collecting data consist of assessment form of nurses on the use of plastic film collector bag. and the record blood volume. This study showed that the plastic film collector bag can measure clearly the blood loss from delivery. There were 4 (4%) postpartum hemorrhage mothers were estimated blood loss more than 500 cc. The professional nurses opinions of the plastic film collector bag found that positive tendency that agree with 80%. They noted that the plastic film is width than 6 inches long, 14 inches and deep 6 inches is appropriate, convenient and easy to use. The precision in the estimation of blood. Useful for the birth and does not increase the workload which should be applied to the process of childbirth as normal